Evaluation of Coverage and Knowledge Levels during a Vaccination Campaign against Yellow Fever, Cusco-Perú, 2005 - Grajeda Ancca, Pablo F. (2023)
Introduction: Yellow Fever (YF) is enzootic in Cusco, and it is a serious public health problem. A National Plan for Control and Prevention of YF was implemented, aiming at vaccinating the whole Peruvian population above 1 year of age in four stages (2004-2007); and it was expected to vaccinate all of Cusco city inhabitants (306,160 persons in this age group) between November 2004 and February 2005. The final coverage reported was 83.5%. The objective of the study was to assess vaccination coverage and knowledge and communication levels of this campaign. Methods: A descriptive, cross-sectional, and prospective study was performed in Cusco in March 2005, using a stratified and randomized sampling technique. 954 people were interviewed in order to assess vaccination coverage and 386 for other objective measures. Results: Vaccination coverage against yellow fever in Cusco was 64.04%. Vaccinated people did not have good knowledge of: what yellow fever is (76.7%), how is it transmitted (50.9%), time in which the vaccine starts to exert its effect (84.9%), duration of the protective effect of the vaccine (92.2%), and contraindications for vaccination (65.2%). Only 0.27% remembered at least one of key messages of the campaign. Conclusions: This assessment showed that the goals for coverage in this vaccination campaign were not achieved; there were large differences between official reports (83.5%) and the results form our survey (64.04%). Immunized population was not adequately informed about the yellow fever vaccine and its vaccination campaign, which leads to question the benefits of performing campaigns affecting some basic bioethical principles.